The Ecological Role and Carbon Sequestration Potential of Mangrove Ecosystems in Sondaken for Climate Change Mitigation - Nurmawan, Wawan; Ogie, Tommy B.; Lasut, Marthen T. (Sam Ratulangi University, 2025)
Mangrove ecosystems play an important ecological role in maintaining coastal environmental balance and contribute significantly to climate change mitigation through carbon sequestration. This study aims to analyse the vegetation structure, zoning, biomass potential, and carbon storage of the mangrove ecosystem in Sondaken, South Minahasa Regency, North Sulawesi, as well as to examine its ecological role in climate change mitigation. Data collection was conducted on ten plots arranged perpendicular to the coastline. The identification results showed that there were ten true mangrove species with a strong dominance of Rhizophora apiculata at all growth levels. The highest Importance Value Index (IVI) was achieved by R. apiculata with 97.83 at the tree level, indicating good adaptability and regeneration. Mangrove zoning is divided into three main parts, namely the back zone (Avicennia and Bruguiera spp.), the middle zone (Rhizophora apiculata and R. mucronata), and the front zone (Sonneratia alba and Avicennia alba). The average biomass value reached 489.37 tonnes/ha, while the average stored carbon was 230 tonnes/ha, indicating high potential as a blue carbon sink. Ecologically, the Sondaken mangrove plays an important role in absorbing atmospheric carbon, protecting the coast from abrasion, and providing habitat for various coastal biota. The results of this study confirm that the Sondaken mangrove ecosystem has high strategic value in climate change mitigation and adaptation and needs to be managed sustainably through conservation and rehabilitation based on natural zoning.